Analysis of the Migration Characteristics of Stormwater Runoff Pollutants on Different Underlying Surfaces in Guangzhou, China - Pan, Yongjun; Li, Zhiqi; Gao, Yaoyao; Xiong, Yongmei; Qiao, Yu; Tao, Yuzhu; Wu, Qiaohua; Lin, Wen; Qi, Yueqiang; Long, Jiayi; Ruan, Lin; Dai, Seping; et al. (Frontiers in Earth Science, 2021)
Stormwater runoff is identified as urban non-point source pollution that increasingly introduces contaminants to urban water bodies and impedes sustainable development. The pollution load of runoff varies due to the interception of different land cover types during the urban hydrological process. During the rainy season (June-August) in 2018, five different underlying surfaces (green roof, parking lot, urban road, parkway and grassland) were selected in Guangzhou to analysis the migration characteristics of stormwater runoff pollutants. The concentrations of heavy metals, such as chromium (Cr), cadmium (Cd), lead (Pb), mercury (Hg), as well as total nitrogen (TN), total phosphorus (TP) and Polycyclic aromatic hydrocarbons (PAHs) were collected and analysed on different underlying surfaces with the rainfall data at the beginning of a stormwater runoff event. The results showed that PAHs, heavy metals and TP existed mainly in the form of particles; nitrogen was mainly present as ammonia and nitrate; and the TN, TP, PAHs and heavy metal were significantly different in the stormwater runoff on each underlying surface. The pollutant concentration in urban road runoff was the highest, accounting for 40% ~ 70% of the total pollutant concentration in the stormwater runoff, and the pollutants concentration in green roof runoff was the lowest, accounting for 10% ~ 40% of the total pollutant concentration in the runoff. An obvious effect of initial rainfall erosion was observed during stormwater runoff from urban roads and parking lots, and the scouring effect on grasslands and green roofs was mainly due to the many factors affecting the underlying surface during the middle and late stages. The rates of reduction of heavy metals was the most significant. The effect of water purification was positively correlated with stormwater runoff duration. The rates of reduction of TN, heavy metals (Cr, Cd and Hg) and PAHs in the grassland areas were 35.20±26.28%, 0.24±10.13%, 71.77±10.97%，32.62±110.48%and 41.30±8.78%, respectively. This study could provide a theoretical basis for preventing and managing pollutants in urban stormwater runoff.